Factors and Characteristics of Workplace Violence Against Nurses: A Study in Iran - Dehghan-Chaloshtari, Sahar; Ghodousi, Arash (Journal of interpersonal violence, 2020)
Violence against nurses is a serious problem that can affect negatively the quality of nursing care. The extent of violence against nurses in Iran and the factors leading to this violence have not been known. Thus, the aim of this study was to investigate all forms of violence against nurses in Shahrekord hospitals in 2014. In this 2014 study, 100 nurses working in Shahrekord’s Hajar, Kashani, and Social Security branch hospitals were studied. Data were collected through standardized questionnaires on workplace violence, as well as demographic data, in health units on five types of violence, including physical and verbal violence, intimidation and bullying, ethnic violence, and violation of chastity. The analysis was done by SPSS (Version 19) software. All nurses indicated that during some period of their work, they had been subjected to at least one type of violence; the highest prevalence of mental violence was belonged to the subtype of intimidation and bullying (91%). The primary agents of violence against nurses were patients and their relatives. Factors such as gender, age, work experience, and nursing shifts played important roles in the distribution of violence. In ethnic violence, the only factor affecting nurses was race (p < .05). The highest rate of violence against nurses was due to mental or psychological violence. To minimize violence in hospitals, authorities should consider appropriate preventive strategies, good management, proper protective measures, and public education.